Evergreen Mediterranean hardwoods as particleboard raw material - Barboutis, John a; Philippou, John L. (Building and Environment, 2007)
Wood and biomass (branches and foliage) of ﬁve Mediterranean evergreen hardwood species (Quercus coccifera, Quercus ilex, Arbutus unedo, Phillyrea latifolia, Erica arborea) growing in Greece were investigated as particleboard raw material. The average diameter of the stems varied between the species from 4.1 cm (Erica arborea) to 7.5 cm (Quercus ilex) and the bark to wood ratio of the stems varied between the species from 7.8% (Quercus ilex) to 15.9% (Erica arborea). Bulk density of particleboard furnishes produced by processing the above materials through a chipper and a ring ﬂaker varied between the species from 143.6 to 162.5 kg/m 3 . Common industrial furnish reached in the used lab conditions a bulk density of 143 kg/m 3 . Particle size and their distribution also varied between the hardwood species. One-layer laboratory particleboards made with the above materials at densities of 650, 700 and 750 kg/m 3 had considerable lower mechanical properties but better dimensional stability than boards made with common industrial furnish. All properties were affected by wood species and board density. Internal bond of all boards was higher than the value required by EN 319/1993 but adequate bending strength at moderate densities (0.70 kg/m 3 ) was achieved only in boards made with Arbutus unedo and Quercus ilex. Boards made with branches and foliage had very low mechanical properties.
Keywords: biomass; mediterranean evergreen hardwoods; particleboard

Evergreen Mediterranean hardwoods as particleboard raw material - Barboutis, John a.; Philippou, John L (Building and Environment, 2007)
Wood and biomass (branches and foliage) of ﬁve Mediterranean evergreen hardwood species (Quercus coccifera, Quercus ilex, Arbutus unedo, Phillyrea latifolia, Erica arborea) growing in Greece were investigated as particleboard raw material. The average diameter of the stems varied between the species from 4.1 cm (Erica arborea) to 7.5 cm (Quercus ilex) and the bark to wood ratio of the stems varied between the species from 7.8% (Quercus ilex) to 15.9% (Erica arborea). Bulk density of particleboard furnishes produced by processing the above materials through a chipper and a ring ﬂaker varied between the species from 143.6 to 162.5 kg/m 3 . Common industrial furnish reached in the used lab conditions a bulk density of 143 kg/m 3 . Particle size and their distribution also varied between the hardwood species. One-layer laboratory particleboards made with the above materials at densities of 650, 700 and 750 kg/m 3 had considerable lower mechanical properties but better dimensional stability than boards made with common industrial furnish. All properties were affected by wood species and board density. Internal bond of all boards was higher than the value required by EN 319/1993 but adequate bending strength at moderate densities (0.70 kg/m 3 ) was achieved only in boards made with Arbutus unedo and Quercus ilex. Boards made with branches and foliage had very low mechanical properties.
Keywords: biomass; mediterranean evergreen hardwoods; particleboard